Angiotensin-converting enzyme genetic variants do not influence response to risperidone in autistic children - Negar Firouzabadi; Nima Ghazanfari; Ali Alavi-Shoshtari; Dena Firouzabadi; Elham Haem (Trends in Pharmaceutical Sciences, 2022)
Genetics has been found to have a prominent role in autism and therefore pharmacogenetics may guide us to a better management of this disorder. Given the importance of Renin-Angiotensin System (RAS) in the function of the brain and its possible association with autism, genetic variations of RAS may influence response to autism treatment. In this study, 83 autistic children were enrolled (3 to 12 years of age). Degree of autism was confirmed by the DSM-V criteria and response to treatment was measured according to Aberrant Behavior Checklist (ABC) scale at baseline, 4 and 12 weeks of risperidone therapy. Polymorphisms (ACE I/D, rs4343 and rs4291) were determined by PCR-RFLP. Our results indicate the positive role of long term therapy in autism (12 weeks vs 4 weeks). The highest response rate in ACE ID gene was in the DD genetic variant at both 4 and 12 weeks of treatment. For the ACE A2350G gene, all genetic variants did not respond well to treatment at 4 weeks, however at 12 weeks, positive response was dominant in the AG genetic variant. Highest response rate in the ACE A240T gene belonged to the AT variant at both 4 and 12 weeks of treatment. However, our results indicate no significant association between ACE gene polymorphisms and response to risperidone therapy in autistic children based on ABC scaling. In conclusion, this study does not support the hypothesis of involvement of RAS genetics in response to risperidone in autistic children. Keywords: Autism, Renin-angiotensin system, Angiotensin-converting enzyme, Genetic polymorphism, Single nucleotide polymorphism. Please cite this article as: Negar Firouzabadi, Nima Ghazanfari, Ali Alavi Shoushtari, Dena Firouzabadi, Elham Haem. Angiotensin-converting enzyme genetic variants does not influence response to risperidone in autistic children. Trends in Pharmaceutical Sciences. 2022;8(3):165-174. doi: 10.30476/TIPS.2022.95522.1148